Carrying the Leviathan: How Turnpike Roads Contributed to the Rise of State Capacity in England During the Eighteenth Century - GÜLSUNAR, EMRAH (Springer Science and Business Media Deutschland GmbH, 2025)
This article examines the potential impact of turnpike roads on the English/British state's increasing capacity during the eighteenth century. The literature implicitly suggests that transportation infrastructures impacted state capacities in Europe only after the arrival of railways during the nineteenth century. This study argues that this may not be the case and hypothesizes that the transportation revolution during the eighteenth century, more specifically the turnpike roads in England, could have had a similar impact before the railways. It uses the number of post towns and per capita excise tax revenues as proxies of state capacity and empirically tests whether the spread of turnpike roads impacted them. Estimation results of two different (2SLS panel and time-series error correction) models show that the diffusion of turnpike roads positively influenced the state capacity in England. They increased the presence of the state and improved its monitoring abilities by enabling better transportation of state officials in their circuits and by reducing journey times between the capital and provinces. These results show that transportation infrastructure was already one of the determinants of state capacity before the railways in England, and turnpike roads were influential not just in economic but also in political development.
Keywords: Eighteenth Century; England; Post Towns; State Capacity; Tax Revenues; Turnpike Roads